CRIMЕ OF MATCH FIXING WITH REVIEW ОN THE COUNCIL OF EUROPE CONVENTION ON THE MANIPULATION OF SPORTS RESULTS - Марјановић, Ђорђе (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Fixing the outcome of sports competitions is one of the biggest threats to the integrity of sports. Sport as a social phenomenon has its own individual and social dimension, however, the degree of benefit for the individual and society can be neutralized by phenomena that threaten the integrity of sports competitions. The goal of this research is to provide an answer to the question of whether criminal law, as a branch of law characterized by the ultima ratio character, should respond to the appearance of fixing the outcome of sports competitions, as well as what type of outcome fixing should be responded to within the framework of criminal law. This research also includes an analysis of certain provisions of the Council of Europe Convention on the manipulation of sports results in order to see the potential scope of the Convention in terms of influence on the criminal legislation of countries that ratify the convention. In the last part of the paper, the criminal offense of fixing the outcome of the competition from Art. 208a. Criminal Code of the Republic of Serbia